2013
DOI: 10.1017/s175297191300016x
|View full text |Cite
|
Sign up to set email alerts
|

Realism, emotion, and dynamic allegiances in global politics

Abstract: This article appeals to classical realism for new insights into the role emotions play in shifting the terrain of political allegiance in global politics. Although undetected in readings emphasizing rational statecraft, realists such as Hans Morgenthau and Reinhold Niebuhr were centrally concerned with human emotions and their political impact. While following the intellectual currents of their time in regarding emotions as fixed impulses, these realists' deep appreciation for the contingencies of history also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…42 Facing current policy dilemmas, Morgenthau's ethics asks for a shift in policymaking and even a reconsideration of its purpose, demonstrating that 'what is important is not so much what public discourse is about as the way in which public discourse takes place.' 43 Morgenthau's ethics does not allow drawing on 'ontological blueprints' 44 to detect social laws upon which the current socio-political status quo can be consolidated. 45 Hence, this ethics criticizes policymaking that turns questions of politics into issues of administration, as it implies that solutions to these practical dilemmas are to be found in the establishment of extensive bureaucracies, rather than engaging with their contested nature.…”
Section: Resultsmentioning
confidence: 99%
“…42 Facing current policy dilemmas, Morgenthau's ethics asks for a shift in policymaking and even a reconsideration of its purpose, demonstrating that 'what is important is not so much what public discourse is about as the way in which public discourse takes place.' 43 Morgenthau's ethics does not allow drawing on 'ontological blueprints' 44 to detect social laws upon which the current socio-political status quo can be consolidated. 45 Hence, this ethics criticizes policymaking that turns questions of politics into issues of administration, as it implies that solutions to these practical dilemmas are to be found in the establishment of extensive bureaucracies, rather than engaging with their contested nature.…”
Section: Resultsmentioning
confidence: 99%
“…Nearly two decades ago Neta Crawford () observed that “realist and idealist discourse about emotions—what has been said and not said about anger, fear, love, empathy, the desire for revenge, and so on—has shaped the discipline in important respects” (p. 156). This call to investigate the emotional underpinnings of key theories and concepts in IR has since been taken up by a number of scholars (e.g., Kertzer & McGraw, ; Ross, ; Solomon, ). However, of the emotional categories Crawford () identified, comparatively little has been said by IR scholars about empathy (key exceptions include Head, , ; White, ).…”
Section: Locating Empathy In Security Dilemma Theorizingmentioning
confidence: 99%
“…Beyond intentionality, various theories of NGOs' human rights advocacy implicitly suggest that NGOs have distinct emotional centers and are part of processes with (unexplored) emotional bases (Clark, ; Finnemore, ; Keck & Sikkink, ; Ross, ). Thus, the conception of NGOs as principled agents part of like‐minded transnational advocacy networks (TANs) (Keck & Sikkink, ) echoes Koschut's () conceptualization of NSAs as “emotional communities.” We also know that depending on their institutional identities, not all NGOs approach shaming or emotional exchanges similarly.…”
Section: The Emotional Diplomacy Of Ngos: Bringing Nonstate Actors Bamentioning
confidence: 99%